Legal Analysis Of Banking Dispute Resolution Through The Consumer Dispute Resolution Agency From The Perspective Of Consumer Protection Law - Muhammad Ali Hadidie Parinduri (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Settlement of banking disputes through BPSK in the protection of banking customers is a legal defect because it is the authority of the Alternative Dispute Resolution Institution for the Financial Services Sector, BPSK is more appropriate for consumer disputes within the scope of industry and trade. The formulation of the problem in this thesis is how is the legal regulation of consumer protection for banking institutions, how is the settlement of banking disputes through alternative institutions in customer protection, and how are the judges' legal considerations in the Supreme Court Decision of the Republic of Indonesia Number 253 K/Pdt.Sus-BPSK/2017. The research method used is descriptive analysis that leads to normative juridical legal research, namely research conducted by referring to legal norms, namely researching library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results of the study indicate that legal regulation of consumer protection for banking institutions is regulated in Law Number 21 of 2011 and Financial Services Authority Regulation (POJK) Number 1/POJK.07/2013 in conjunction with Number 1/POJK.07/2014. Settlement of banking disputes through alternative institutions in customer protection is settlement by Arbitration between bank customers and the banking sector is the authority of the Alternative Dispute Settlement Institution for the Financial Services Sector. The judge's legal considerations after carefully examining the memorandum of cassation dated December 7, 2016 and the counter memorandum of cassation dated December 28, 2016 are related to Judex Facti's considerations, in this case The Kisaran District Court is not wrong in applying the law because the a quo case is a breach of contract that originates from a credit agreement.